The Effect of Protein Fusions on the Production and Mechanical Properties of Protein‐Based Materials. (27th January 2015) - Tsai, Shang‐Pu; Howell, David W.; Huang, Zhao; Hsiao, Hao‐Ching; Lu, Yang; Matthews, Kathleen S.; Lou, Jun; Bondos, Sarah E.
Abstract : Proteins implement most of the vital molecular functions of living organisms, including structural support, energy generation, biomolecule sensing, and chemical catalysis, storage, and degradation. While capturing proteins in materials could create devices that mimic these functions, this process is challenging due to the sensitivity of protein structure to the chemical environment. Using recombinant DNA methods, specific functions can be incorporated by fusing the gene encoding a self‐assembling protein and the desired functional protein, to produce a single polypeptide that self‐assembles into functionalized materials. However, the functional protein has the potential to disrupt protein production, protein assembly, and/or the structure and mechanical properties of the resulting materials. 24 fusion proteins are created based on Ultrabithorax, a Drosophila transcription factor that self‐assembles into materials in vitro. The appended proteins dictate the solubility and purification yield of the corresponding protein fusions. Any loss of solubility and yield can be mitigated by fusing a third protein that is highly soluble. All protein fusions self‐assemble equally well to produce materials with similar morphologies. Fusing enhanced green fluorescent protein to Ultrabithorax influences mechanical properties of the resulting fibers. It is concluded that a far wider range of proteins can be successfully incorporated into elastomeric protein‐based materials than originally anticipated. Abstract : A wide range of proteins can be incorporated into protein‐based materials via gene fusion, to produce a single polypeptide capable of self‐assembly and the function of interest. 24 proteins are fused to Ultrabithorax, a protein which self‐assembles in vitro. Whereas the appended proteins determine the solubility and purification yield of the corresponding fusion protein, all fusion proteins self‐assemble equally well.